Greatest mysteries of the unexplained a compelling collection of the world's most perplexing phenomena - Doncaster, Lucy (Arcturus Publishing Limited, 2012)
Examines strange and unexplained phenomena, including disappearances, ghosts, curses, wierd nature, UFO's and more.